The role of nutritional treatment in postsurgical convalescence process - Ewa Rzeska; Karolina Jurasz; Dominika Podgórska; Radosław Cymer; Miłosz Sanecki; Karolina Tomczyk; Natalia Chojnacka; Jakub Klarycki (Nicolaus Copernicus University in Toruń, 2024)
The article discusses the importance of adequate nutrition for patients suffering from serious illnesses, such as those requiring surgery. Despite medical advances, malnutrition remains a challenge for practitioners. The authors described the importance of nutritional support for patients in critical care, short bowel syndrome and after bariatric surgery. The text highlights the difficulties and challenges of nutritional treatment, such as malnutrition, overweight, and the need to adapt nutritional practices to the latest guidelines and research. The article also emphasizes the importance of educating patients about the benefits of nutritional treatment and the need for access to dietary counseling at every stage of the disease. The role of artificial intelligence in nutritional treatment and the need for further research and innovation in this area are also addressed. The paper describes the different methods of nutrition - enteral and parenteral, their advantages and risks, and notes the need for an individualized approach to each patient, taking into account their condition, age, gender, height and weight.  Ultimately, the article emphasizes the importance of access to health care and education to increase the effectiveness of nutrition treatment.